Controlled Growth of MoS2 Nanosheets on 2D N‐Doped Graphdiyne Nanolayers for Highly Associated Effects on Water Reduction. (15th March 2018) - Yu, Huidi; Xue, Yurui; Hui, Lan; Zhang, Chao; Zhao, Yingjie; Li, Zhibo; Li, Yuliang
Abstract: The first utilization of nitrogen‐doped graphdiyne (NGDY) as an efficient catalytic promoter for hydrogen evolution reaction (HER) is reported. X‐ray powder diffraction and X‐ray photoelectron spectroscopy studies indicate the presence of strong interactions between NGDY and MoS2, which should effectively facilitate the charge transport behavior and improvement of the HER kinetics. The creative hybridization of MoS2 and NGDY endows such heterostructure with structural and compositional advantages for boosting the catalytic activity (low overpotential of 186 mV at 10 mA cm −2 and Tafel slope of 63 mV dec −1 ) and extraordinary stability (higher than all reported MoS2 ‐based materials and even better than that of commercial Pt and almost all benchmarked electrocatalysts). All of the results not only demonstrate that NGDY can be used as an effective catalytic promoter for hydrogen production, but also provide new strategy for fabricating efficient water‐splitting electrodes. Abstract : The creative hybridization of MoS2 and nitrogen‐doped graphdiyne endows such heterostructure with structural and compositional advantages and highly associated interactions, which effectively facilitate the charge transport behavior and hydrogen evolution reaction (HER) kinetics, leading to greatly enhancement in the intrinsic HER catalytic activities and outstanding stability in acidic conditions.